Effect of the Active Layer Thickness of Pentacene Thin Film Transistor; Illumination Effect - Yousfi, Y.; Jouili, A.; Mansouri, S.; El Mir, L.; Al-Ghamdi, Ahmed; Al-Sehemi, Abdullah G.; Yakuphanoğlu, Fahrettin (Springer, 2021)
In this study, we examine the performance of organic field-effect transistors (OTFTs), based on pentacene as an active layer. We investigate two different thicknesses of pentacene film (280 nm and 150 nm) deposited on a poly(4-vinylphenol) layer grown on a SiO2 dielectric layer. To compare the functioning of these two pentacene OTFTs (280 nm and 150 nm), we analyze the electrical parameters, particularly the mobility mu, the threshold voltage V-th, the I-on/I-off ratio, the sub-threshold swing S, the interface concentration of trap states D-it, the total concentration of traps that are filled per unit volume N-trap and the photoresponsivity R. The calculation of these parameters was under different intensities of white light illumination and for V-g = -14 V. We observed that the OTFT with a thinner layer of pentacene (150 nm) exhibits better performance for V-g = -14 V under 100 mW/cm(2) than the other OTFT with a thicker active layer (280 nm). Moreover, we adopt a model based on the variable range hopping approach in order to examine the Gaussian density of states (DOS) distribution, the mobility and the Seebeck coefficient of pentacene OTFTs under obscurity and various intensities of white light illumination. Finally, we explain the strong dependence of the electrical parameters of pentacene OTFTs (the DOS distribution, and the Seebeck coefficient) on both illumination and width of the pentacene film.
Keywords: SiO2-PVP-pentacene-TFT; pentacene thickness effect; illumination effect; simulation